Optimizing of near infrared region reflectance of mix-waste tile aggregate as coating material for cool pavement with surface temperature measurement - Anting N.; Din M.F.M.; Iwao K.; Ponraj M.; Siang A.J.L.M.; Yong L.Y.; Prasetijo J. (Elsevier Ltd, 2023)
Aggregates; Asphalt; Coatings; Design of experiments; Infrared devices; Plating; Porcelain; Reflection; Surface properties; Temperature measurement; Environmental problems; High-energy absorption; Near infrared region; Reflectance values; Surface reflectance; Surface temperature measurement; Surface temperatures; Urban heat island; Atmospheric temperature